Giant resistive switching in mixed phase BiFeO3via phase population control. Issue 37 (11th September 2018) - Edwards, David; Browne, Niall; Holsgrove, Kristina M.; Naden, Aaron B.; Sayedghaee, Sayed O.; Xu, Bin; Prosandeev, Sergey; Wang, Dawei; Mazumdar, Dipanjan; Duchamp, Martial; Gupta, Arunava; Kalinin, Sergei V.; et al.
Abstract : Giant resistive switching is achieved through control of mixed-phase microstructures in BiFeO3 via different stimuli. Abstract : Highly-strained coherent interfaces, between rhombohedral-like (R) and tetragonal-like (T) phases in BiFeO3 thin films, often show enhanced electrical conductivity in comparison to non-interfacial regions. In principle, changing the population and distribution of these interfaces should therefore allow different resistance states to be created. However, doing this controllably has been challenging to date. Here, we show that local thin film phase microstructures (and hence R–T interface densities) can be changed in a thermodynamically predictable way (predictions made using atomistic simulations) by applying different combinations of mechanical stress and electric field. We use both pressure and electric field to reversibly generate metastable changes in microstructure that result in very large changes of resistance of up to 10 8 %, comparable to those seen in Tunnelling Electro-Resistance (TER) devices.